(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the problems of a development of the political crisis in France in the 1559-1562. Basing on the analysis of the set of events end processes the author makes an attempt to give her on definition of the public conflict character of the time and to specify the date then the civil wars started.